Incentivando o engajamento discursivo com a língua inglesa por meio de personagens animados: abrindo a porta para os monstros na educação infantil - Rodrigues, Taiana Veiga Dias (2018)
The present thesis presents and discusses an action-research intervention carried out at a municipal school in the outskirts in the city of Bagé, RS, in 2017. The general objective of this thesis is to produce, implement and evaluate a pedagogical product aimed at a practice of transmedia teaching and learning, analyzing the role of multisemiotic resources with the English language learning in children's education. Through the intervention, a didactic unit was applied taking as background the animation Monsters, Inc. (2001), since it is understood the importance of cartoons for the child development and its possibility of usage in the classroom, as Barbosa (2013) and Silva (2001) point out. Once introducing the animation as a resource for the classes, it was sought to encourage discursive engagement with the English language, searching to engage a dialogue with the Multiliteracy and Transmedia concepts, providing a meaningful learning in the classroom. In the intervention development, it was investigated in which ways the students were engaged discursively, in view of different multisemiotics or multimodal resources as explained by Prediger and Kersch (2013). Thus, this dissertation was based on authors such as Chaguri and Tonelli (2013), Magalhães (2013) and Leventhal (2010) when addressing the teaching of the English language in children's education and its assumptions. In dealing with Multiliteracy and Transmedia, it’s introduced authors who, in approaching relation to these two concepts, could by some means relate to the language teaching in children's education, for example, Rocha (2014), Cope e Kalantzis (2000), Lemke (2010) and Jenkins (2010). On the discursive engagement it’s connected the National Curricular Parameters (1998) and Rocha (2010) and concerning the significant learning we present authors such as Tonelli (2005) and Moreira (2012). The didactic unit, presented in the pedagogical product in this thesis, shows activities and objectives created based on suggestions from authors as Assumpção (2012), Richards (2008) and Roth (1998). The product was elaborated, implemented and evaluated, verifying if the intended objectives at the beginning of the work were actually achieved. The evaluation was based on the data obtained during the intervention, such as the use of photos, audio and video recording and the reflective journal. Thus, at the end of the intervention, it was understood to be possible the dialogue between Multiliteracy and Transmedia with English language classes in early childhood education, comprehending the importance of relating the concepts with meaningful learning, creating links for children, in a way in which their learning does not become detached from their lives.